Beyond Persuasion : Communication Strategies for Healthcare Managers in the Digital Age - PATRICIA J. PARSONS (University of Toronto Press, 2013)
The advent of social media has forever changed how organizations communicate with the public, and healthcare organizations are no exception. Beyond Persuasion provides healthcare managers with a guide to using strategic communication to meet both personal and professional objectives in the digital age. Whether healthcare managers are conducting meetings with employees, answering massive amounts of email, or keeping up with Twitt er feeds, their success ultimately depends on their strategic communication skills. The fi rst book to off er a strategic approach to managerial communication in health care, Beyond Persuasion is full of valuable information on issues such as how to develop fundamental skills, communicate strategically with internal groups such as employees and medical staff , and develop relationships with the external community and both traditional and new media